Safer Patients Empowered to Engage and Communicate about Health (SPEECH) in primary care: a feasibility study and process evaluation of an intervention for older people with multiple long-term conditions (multimorbidity) - Rebecca Goulding; Kelly Birtwell; Mark Hann; Sarah Peters; Harm van Marwijk; Peter Bower (BMC Primary Care, 2024)
Abstract Background Older people with multiple long-term conditions (multimorbidity) (MLTC-M) experience difficulties accessing and interacting with health and care services. Breakdowns in communication between patients and staff can threaten patient safety. To improve communication and reduce risks to patient safety in primary care, we developed an intervention: Safer Patients Empowered to Engage and Communicate about Health (SPEECH). SPEECH comprises a booklet for patients and an associated guide for staff. The booklet is designed to provide patients with information about staff and services, skills to prepare and explain, and confidence to speak up and ask. Methods A single-arm mixed methods feasibility study with embedded process evaluation. General practices in the North West of England were recruited. Participating practices invited patients aged 65+ with MLTC-M who had an appointment scheduled during the study period. Patients were asked to complete questionnaires at baseline and follow-up (four to eight weeks after being sent the patient booklet), including the Consultation and Relational Empathy measure, Empowerment Scale, Multimorbidity Treatment Burden Questionnaire, and Primary Care Patient Measure of Safety. Staff completed questionnaires at the end of the study period. A sub-sample of patients and staff were interviewed about the study processes and intervention. Patients and the public were involved in all aspects of the study, from generation of the initial idea to interpretation of findings. Results Our target of four general practices were recruited within 50 days of the study information being sent out. A fifth practice was recruited later to boost patient recruitment. We received expressions of interest from 55 patients (approx. 12% of those invited). Our target of 40 patient participants completed baseline questionnaires and were sent the SPEECH booklet. Of these, 38 (95%) completed follow-up. Patients found the intervention and study processes acceptable, and staff found the intervention acceptable and feasible to deliver. Conclusions Our findings suggest the intervention is acceptable, and it would be feasible to deliver a trial to assess effectiveness. Prior to further evaluation, study processes and the intervention will be updated to incorporate suggestions from participants. Trial registration The study was registered on the ISRCTN registry (ISRCTN13196605: https://doi.org/10.1186/ISRCTN13196605 ).